Digital Transformation of Maritime Education Management: Technology-Based Performance Systems and Lecturer Productivity in Indonesian Institutions - Suhartini Suhartini; Marudut Bernadtua Simanjuntak (IJECA (International Journal of Education and Curriculum Application), 2026)
Digital transformation fundamentally reshapes academic work environments, yet maritime education institutions under Ministry of Transportation governance face distinctive challenges implementing technology-based management systems while maintaining lecturer wellbeing and institutional effectiveness. This convergent parallel mixed-methods research investigates how digital performance monitoring platforms, administrative systems, learning analytics, and e-leadership practices influence lecturer job satisfaction, organizational commitment, technostress, research productivity, and teaching effectiveness across fourteen Indonesian maritime higher education institutions. Through in-depth interviews with 425 lecturers, 58 administrators, 42 policy officials, and 35 technology specialists, combined with focus groups, organizational ethnography, and thematic analysis, this study reveals paradoxical technology impacts: while certain systems enhanced efficiency and pedagogical innovation, poorly implemented digital tools increased administrative burden (91% reporting), reduced perceived autonomy (87%), elevated technostress (64%), and negatively affected job satisfaction (71% negative intrinsic satisfaction). Critical moderating factors emerged including e-leadership effectiveness (91% successful implementations), participatory implementation approaches (88%), comprehensive professional development (87%), user-centered system design (94%), and robust technical support (84%). The research contributes the Maritime Academic Technology Impact Framework (MATIF) providing evidence-based implementation guidelines for administrators and policy officials pursuing digital transformation while protecting academic workforce sustainability within Ministry of Transportation governance contexts.